Medial temporal atrophy in posterior cortical atrophy and its relationship to the cingulate island sign. (20th December 2022) - Josephs, Kennedy A; Pham, Nha Trang Thu; Graff‐Radford, Jonathan; Machulda, Mary M.; Lowe, Val J.; Whitwell, Jennifer L
Abstract: Background: Posterior cortical atrophy (PCA) is associated with hypometabolism on FDG‐PET and atrophy on MRI in the parietal and occipital lobes, and patients often show the cingulate island sign (CIS) whereby posterior cingulate metabolism is relatively spared compared to the precuneus and cuneus. It has been hypothesized that medial temporal sparing may be related to CIS in PCA. We aimed to assess the severity of medial temporal atrophy in PCA and determine whether the presence of a CIS is related to medial temporal sparing. Method: Fifty‐five PCA patients underwent a 3T volumetric MRI and FDG‐PET. The degree and symmetry of medial temporal atrophy on MRI was visually assessed in both hemispheres using the five‐point Scheltens scale (0=normal; 1=mild; 2=moderate; 3=marked; 4=severe). Visual assessments of FDG‐PET coded the presence/absence of a CIS and whether the CIS was symmetric or asymmetric. Hippocampal volumes and a quantitative CIS were also measured. Associations between medial temporal atrophy scores and clinical measures were assessed using linear regression correcting for age. Result: Medial temporal atrophy was most commonly mild (38% on the right, 40% on the left), followed by moderate (35% on the right, 29% on the left), and then no atrophy (18% on right, 25% on left). Marked or severe atrophy was only observed in 9% of patients on the right and 5% of patients on the left. Atrophy was asymmetric in 55%, and when asymmetric was most commonly worse on the right (76%). Greater medial temporal atrophy was associated with older age (p<0.001) and worse verbal episodic memory (p=0.008). The CIS was observed in 44% of the PCA patients and was asymmetric in 50% of these. The patients with a CIS showed greater medial temporal asymmetry (p=0.016), but did not show lower medial temporal atrophy scores, compared to those without a CIS. Hippocampal volumes were not associated with quantitative CIS. Conclusion: Mild to moderate medial temporal atrophy is a common finding in PCA and is associated with worse memory impairment and older age. However, medial temporal sparing was not related to the presence of a CIS in PCA.